2001
DOI: 10.2134/agronj2001.934896x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production of ‘Alamo’ Switchgrass in Response to Nitrogen, Phosphorus, and Row Spacing

Abstract: yr Ϫ1 ; Wolf and Fiske, 1995; Brejda, 2000). The compromise between yield and quality does not apply to bio-Management practices for biomass production of bioenergy grasses mass production for bioenergy feedstock because the may differ from management for forage. Our objective was to determine the yield and stand responses of 'Alamo' switchgrass (Panicum goal generally is to maximize production of lignocelluvirgatum L.) to N and P fertilization as affected by row spacing. A lose (Sanderson et al., 1999a). Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
182
3
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(211 citation statements)
references
References 16 publications
21
182
3
5
Order By: Relevance
“…ischaemum), and native ranges that included switchgrass in Oklahoma [29]. Unlike a previous study where no yield response to 39 kg Pha −1 was observed for switchgrass in Texas [5], the increased yield obtained with 45 kg Pha −1 in this study may have resulted from better stand development, increased soil plant available P, and better P scavenging by the roots. The low P response may be due to inherent ability of switchgrass to efficiently use P or extract fixed P in the soil.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…ischaemum), and native ranges that included switchgrass in Oklahoma [29]. Unlike a previous study where no yield response to 39 kg Pha −1 was observed for switchgrass in Texas [5], the increased yield obtained with 45 kg Pha −1 in this study may have resulted from better stand development, increased soil plant available P, and better P scavenging by the roots. The low P response may be due to inherent ability of switchgrass to efficiently use P or extract fixed P in the soil.…”
Section: Discussioncontrasting
confidence: 76%
“…However, there is limited information on its fertilizer requirement including phosphorus (P) rates needed to optimize biomass yields. Previous research in this region has generally shown that switchgrass biomass yields respond to nitrogen (N) fertilizer rates of up to 168 kg ha −1 , depending on ecotype and location [4][5][6]. Phosphorus, a plant macronutrient reported to limit plant growth and productivity in 40% of the world's arable soil [7], is a constituent of macromolecular structures like nucleic acids and is critical for synthesis of energy transfer organic compounds such as adenosine triphosphate in plants [8].…”
Section: Introductionmentioning
confidence: 99%
“…Switchgrass did not respond to applied P in Texas 25 or in low P soils in Iowa. 28 However, research in Nebraska suggested switchgrass may respond to applied P if P availability in the soil is low.…”
Section: Establishing and Managing Switchgrassmentioning
confidence: 87%
“…However, Stephenville and Beeville, respectively. 25 Biomass production declined over years without applied N, and was sustainable only with the application of at least 168 kg N ha −1 yr −1 . In Alabama, Ma et al 26 reported switchgrass yields increased as N rate increased up to 224 kg N ha −1 .…”
Section: Establishing and Managing Switchgrassmentioning
confidence: 99%
“…Extensive soil testing has revealed that a substantial percentage of acres in the southern Great Plains are deficient in potassium (K), primarily those in the eastern areas that are comprised of sandy soils and receive greater than 889 mm of rainfall each year [2]. At present, most switchgrass fertilizer management studies have mainly focused on the benefits and costs associated with nitrogen (N) fertilizer as the primary limiting nutrient [3][4][5] and a few studies have focused on phosphorus (P) fertilizer [1,6,7]. However, little information is available regarding the costs and benefits associated with N and K fertilization on switchgrass produced in K-deficient soils.…”
Section: Introductionmentioning
confidence: 99%